Peran Komitmen Organisasional Terhadap Kinerja Tenaga Keperawatan Pada Rumah Sakit Jiwa Naimata Kupang - Richard H. Mone; Ridolof W. Batilmurik; Amram Rohi Bire (FKIP, Universitas Palangka Raya, 2020)
This study aims to determine and analyze the role of organizational commitment to the performance of nurses at RSJ Naimata Kupang. Naimata Kupang Mental Hospital is the only mental hospital in NTT province that is tasked with providing care for mental and psychiatric disorders. Good nurse performance can be achieved through organizational commitment that provides a strong bond between nurses and mental hospitals, hospitals. This study used a sample of 44 nurses from a total of 79 existing nurses with the 5% Slovin withdrawal technique. The data analysis used multiple linear regression with hypothesis testing either partially or simultaneously. The results of the analysis show that both partially and simultaneously affective, normative and continuous commitment have a positive and significant effect on nurse performance.